2020
DOI: 10.1109/access.2020.3020143
|View full text |Cite
|
Sign up to set email alerts
|

Modified ADRC for Inertial Stabilized Platform With Corrected Disturbance Compensation and Improved Speed Observer

Abstract: In this article, a modified scheme of nonlinear active disturbance rejection control (ADRC) is proposed by correcting the disturbance compensation and improving the speed observer. The stability, disturbance rejection and tracking performance of the modified ADRC scheme are analyzed and compared with that of the typical ADRC scheme utilizing the describing function method and numerical method, which shows that the dynamic stiffness and tracking performance are significantly improved while the stability almost … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(1 citation statement)
references
References 29 publications
0
0
0
Order By: Relevance
“…Several studies have demonstrated the successful application of ADRC in different control systems with impressive control performance [6][7][8]. Additionally, combining ADRC with the inertia control method has resulted in significant improvements in system frequency fluctuation amplitude and settling time [9][10].…”
Section: Introductionmentioning
confidence: 99%
“…Several studies have demonstrated the successful application of ADRC in different control systems with impressive control performance [6][7][8]. Additionally, combining ADRC with the inertia control method has resulted in significant improvements in system frequency fluctuation amplitude and settling time [9][10].…”
Section: Introductionmentioning
confidence: 99%